2018
DOI: 10.1152/physiol.00019.2017
|View full text |Cite
|
Sign up to set email alerts
|

Starring or Supporting Role? Satellite Cells and Skeletal Muscle Fiber Size Regulation

Abstract: Recent loss-of-function studies show that satellite cell depletion does not promote sarcopenia or unloading-induced atrophy, and does not prevent regrowth. Although overload-induced muscle fiber hypertrophy is normally associated with satellite cell-mediated myonuclear accretion, hypertrophic adaptation proceeds in the absence of satellite cells in fully grown adult mice, but not in young growing mice. Emerging evidence also indicates that satellite cells play an important role in remodeling the extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 191 publications
3
96
0
4
Order By: Relevance
“…However, we cannot provide evidence for the origin of these central nuclei since our experimental design did not include tissue labelling of markers for SCs or differentiating myoblasts, still our data would be consistent with a small flux of myonuclei through the sequential atrophy and re‐growth processes following nerve crush. This issue certainly deserves further attention (see also below) especially in the light of recent observations evidencing that genetic reduction/ablation of the SC pool in adult (>4‐month‐old) mice does not prevent myofibre growth in response to loading or myofibre re‐growth following atrophy in adult animals (>4 month old) see however; reviewed in …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot provide evidence for the origin of these central nuclei since our experimental design did not include tissue labelling of markers for SCs or differentiating myoblasts, still our data would be consistent with a small flux of myonuclei through the sequential atrophy and re‐growth processes following nerve crush. This issue certainly deserves further attention (see also below) especially in the light of recent observations evidencing that genetic reduction/ablation of the SC pool in adult (>4‐month‐old) mice does not prevent myofibre growth in response to loading or myofibre re‐growth following atrophy in adult animals (>4 month old) see however; reviewed in …”
Section: Discussionmentioning
confidence: 99%
“…Originating from theory that the DNA of a nucleus can support but a limited cellular volume and that this relationship sets a ceiling for growth (; myonuclear domain, MND), major alteration in fibre size should be accompanied by either a reduction of total number of myonuclei or the recruitment and incorporation of de novo formed myonuclei deriving from the regional stem cell niche, ie, Satellite cell (SC) niche . As currently debated, more recent data suggest that both significant atrophy and hypertrophy can occur without changes to number of myonuclei or replenishment of myonuclei from the SC cell niche . Evidence provided (see references above) suggest that skeletal muscle atrophy associated with chronic systemic diseases and/or ageing are instigated by alteration in the balance of atrophy and hypertrophy stimuli and/or dysfunction of the replenishment of myonuclei from the satellite cell niche and/or disturbed innervation.…”
Section: Introductionmentioning
confidence: 99%
“…83 However, there is evidence that exhaustion of the SC pool might not concur to sarcopenia while leading to defective regeneration following acute muscle injury and contributing to age-related muscle fibrosis. 86 In this perspective, the decrease in the SC number associated with sedentary aging individuals as well as altered SC properties as mentioned earlier might impact muscle mass and performance as seen in sarcopenia. Yet the greater extent of age-related muscle fibrosis, a hallmark of sarcopenia, in a background of genetic ablation of SCs 84 suggests that altered SC properties might concur to sarcopenia given the accepted role of SCs in regulating the extracellular matrix.…”
Section: Deranged Satellite Cell Propertiesmentioning
confidence: 93%
“…The initial enthusiasm about the finding that growth differentiation factor 11 (GDF11), a myostatin homologue, might support muscle trophism and regeneration and contrast muscle aging 80 was dampened by reports showing that, on the contrary, GDF11 levels increases with age and inhibits muscle regeneration, behaving like transforming growth factor-β and sharing with it intracellular signalling pathways, 81 and is not a rejuvenator of aged skeletal muscle SCs. 86 In addition, as pointed out recently, 87 the daily life of aged mice in which SCs had been genetically ablated is not comparable with that of aged humans in terms of physical activity and occasional muscle injury in the course of bouts of intense physical strain, which calls for caution in the interpretation of results obtained with animal models of sarcopenia as Figure 3 Extrinsic and intrinsic, cell-autonomous factors concurring to determine changes in SCs with aging ultimately leading to reduced SCs' ability to maintain muscle mass (sarcopenia). 83 However, there is evidence that exhaustion of the SC pool might not concur to sarcopenia while leading to defective regeneration following acute muscle injury and contributing to age-related muscle fibrosis.…”
Section: Deranged Satellite Cell Propertiesmentioning
confidence: 99%
“…Further complication arises from a recent murine study that reported training‐induced increases in myonuclear density but found no evidence for a retention of these newly recruited myonuclei that would last over a subsequent period of detraining (Dungan et al, 2019). Therefore it does not surprise that the question as to the overall contribution of SC fusion in resistance exercise adaptation is a matter of ongoing debate (Gundersen, 2016; Murach et al, 2018).…”
Section: Transcriptional Memory Enables Learning From Experiencementioning
confidence: 99%